Restorative Justice in the Implementation of Diversion Against Child Criminal Victims - Irhammudin, Irhammudin; Edrisy, Ibrahim Fikma (Nurani, 2022)
One solution that can be taken in handling cases of child crime is a restorative justice approach. Therefore, Police investigators are required to have the right options to carry out diversion activities in handling child criminal cases. The purpose of this study was to examine the implementation of restorative justice by North Lampung Police investigators and the victims’ in carrying out diversion. The method used in this study is the normative legal method. The approach used is an empirical juridical approach, in this case relating to the implementation of restorative justice in the implementation of diversion against victims of child crime. This research conducted in Polres Lampung Utara, Indonesia. Based on the results of the study, it was concluded that restorative justice refers to the second precept in Pancasila and carrying out the investigation based on the provisions of KUHAP, Law concerning the Juvenile Criminal Justice System, Law concerning Child Protection and Law concerning Child Protection. Meanwhile, the implementation of restorative justice is to prevent the repetition of criminal acts committed by children and keep children away from the negative influences and implications of the judicial process. The inhibiting factors are the lack of coordination between agencies carrying out diversion at the investigation level, understanding of the meaning of diversion, lack of public trust in the rules for implementing diversion and regulations regarding supervision of the implementation of the results of the diversion agreement.